PENERAPAN RETORIKA DAKWAH DI PONPES PERSATUAN ISLAM GARUT : Analisis Mengajar Ustadz Iqbal Santoso - Mustaqima, Fathi Umar (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
As social beings, humans always communicate with others. Every human being is required to communicate and be rhetorical, skilled at expressing thoughts, ideas, ideas, and feelings. Skilled at capturing the information obtained and also openly conveying the information received. According to Plato, rhetoric is the art of words which can be used to win the souls of many people. This understanding emphasizes that everyone must be proficient in stringing words well in front of an audience so that those who hear can be hypnotized by the words spoken by that person. The application of Ustad Iqbal Santoso's da'wah rhetoric is something that is inherent in da'wah containing da'wah messages that he conveys which are very easily accepted by the students of the Garut Islamic Unity Islamic Boarding School. With all his simplicity, it is clear that his personality is stunning and admirable. Sebagai makhluk sosial, manusia selalu berkomunikasi dengan orang lain. Setiap manusia dituntut terampil berkomunikasi dan beretorika, terampil menyatakan pikiran, gagasan, ide, dan perasaan. Terampil menangkap informasi-informasi yang didapat dan terampil pula menyampaikan informasi-informasi yang diterima. Menurut Plato, retorika ialah seni kata-kata yang dapat digunkan untuk merebut jiwa banyak orang. Pengertian tersebut lebih menekankan bahwa setiap orang harus cakap dalam merangkai kata dengan baik di hadapan khalayak sehingga yang mendengar pun dapat terhipnotis dengan kata-kata yang diucapkan oleh seseorang tersebut. Penerapan retorika dakwah Ustad Iqbal Santoso adalah hal yang melekat dalam dakwah berisi pesan dakwah yang beliau sampaikan sangat mudah diterima oleh santri-santri Ponpes Persatuan Islam Garut. Dengan segala kesederhanaan beliau, tampak jelas kepribadian beliau yang memukau dan mengagumkan.